Concise Review: Canine Diabetes Mellitus as a Translational Model for Innovative Regenerative Medicine Approaches. (5th February 2019) - Moshref, Maryam; Tangey, Bonnie; Gilor, Chen; Papas, Klearchos K.; Williamson, Peter; Loomba-Albrecht, Lindsey; Sheehy, Paul; Kol, Amir
Abstract: Diabetes mellitus (DM) is a common spontaneous endocrine disorder in dogs, which is defined by persistent hyperglycemia and insulin deficiency. Like type 1 diabetes (T1D) in people, canine DM is a complex and multifactorial disease in which genomic and epigenomic factors interact with environmental cues to induce pancreatic β-cell loss and insulin deficiency, although the pathogenesis of canine DM is poorly defined and the role of autoimmunity is further controversial. Both diseases are incurable and require life-long exogenous insulin therapy to maintain glucose homeostasis. Human pancreatic islet physiology, size, and cellular composition is further mirrored by canine islets. Although pancreatic or isolated islets transplantation are the only clinically validated methods to achieve long-term normoglycemia and insulin independence, their availability does not meet the clinical need; they target a small portion of patients and have significant potential adverse effects. Therefore, providing a new source for β-cell replacement is an unmet need. Naturally occurring DM in pet dogs, as a translational platform, is an untapped resource for various regenerative medicine applications that may offer some unique advantages given dogs' large size, longevity, heterogenic genetic background, similarity to human physiology and pathology, and long-term clinical management. In this review, we outline different strategies for curative approaches, animal models used, and consider the value of canine DM as a translational animal/disease model for T1D in people. Stem Cells Translational Medicine 2019;8:450–455 : Abstract : Dogs suffer from spontaneous diabetes mellitus that mirrors certain clinical-pathologic aspects of type 1 diabetes in people. In this Concise Review, we outline different strategies for curative approaches, animal models used, and consider the value of canine diabetes mellitus as a translational animal/disease model for type 1 diabetes in people.